1997
DOI: 10.1046/j.1365-2168.1997.02659.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy and the umbilicus

Abstract: The significant incidence of umbilical defects in patients undergoing laparoscopic surgery calls for accurate diagnosis and good technique. The incidence of incisional hernia might be reduced by avoiding unnecessary wound extension and the use of non-absorbable sutures for defects larger than 2 cm and in men with umbilical hernia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
2
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 19 publications
1
12
2
2
Order By: Relevance
“…For this reason, many surgeons elect to dissect out these defects, use them for their portals of entry, and then repair them in a formal fashion. The 14% incidence of umbilical fascial defects in this study agrees with the 12% to 18% incidence reported by others [9,10].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…For this reason, many surgeons elect to dissect out these defects, use them for their portals of entry, and then repair them in a formal fashion. The 14% incidence of umbilical fascial defects in this study agrees with the 12% to 18% incidence reported by others [9,10].…”
Section: Discussionsupporting
confidence: 93%
“…Nassar et al [9] and Ramachandran [10] reported an incidence of trocar-site herniation at the umbilicus after laparoscopic surgery of 2.2% and 1.6%, respectively, whereas the current study noted an incidence of only 0.8%. Azurin et al [3], using a retrospective chart review, reported an incidence of 0.77% (10), and other authors hayed claimed incidences of I% and 1.5% [6,8].…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The extension of the umbilical fascial defect for removing the gallbladder from the abdomen is the factor predisposing the development of a hernia. 25 The singleport device already necessitates a larger fascial incision for insertion.…”
mentioning
confidence: 99%
“…3 Overall, worldwide, only 5 cases of strangulation requiring emergency bowel resection have been reported following herniation through a 5-mm port site. [5][6][7][8] Multiple risk factors such as trocar diameter, 9 insertion of drains, 5 obesity, 10,11 prolonged manipulation, reinsertion of the ports and increased duration of surgery, 11,12 preexisting hernias, 10 and medical comorbidities 12,13 have been implicated in the development of port-site hernias, but there are very few prospective studies and no randomized studies conducted to identify these hernias. There is no difference between closed-entry and openentry laparoscopic techniques, when fascial closure is undertaken, in the incidence of port site umbilical hernias.…”
Section: Discussionmentioning
confidence: 98%